Analysis Of Online Promotional Strategies At Azka Salon and Spa Muslimah Makassar - Arka Damayanti; Mustakim Mustakim (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Azka Salon and Spa Muslimah is a beauty care business specifically for Muslim women that has lasted for 16 years and has 4 branches spread across Makassar. Such a business requires an optimal marketing strategy in today's advanced era in order to survive and compete. So this article aims to analyze the online promotion strategy used by Azka Salon and Spa Muslimah. This type of research is descriptive qualitative to tell problem solving based on the data that has been collected by presenting, analyzing, and interpreting the data obtained. There are two data sources used, namely primary and secondary data sources originating from the Koran, articles, books, journals, business websites to social media (facebook, Instagram and tick tok) Azka Salon and Spa Muslimah. As for the results obtained, Azka Salon's online promotion strategy has been implemented optimally. This is inseparable from Azka Salon's consistency in uploading interesting content and having a special promotion team that has made it last until now